Analisis Struktur Puisi Karya Perempuan dalam Majalah Suara ‘Aisyiyah - David Setiadi; Asep Firdaus (Jentera: Jurnal Kajian Sastra, 2024)
This research focuses on examining poems published in Suara 'Aisyiyah magazine in the "Aksara" rubric written by Cheny Kurata A'yun, which in quantity appears frequently in the 2021 publication period. This research aims to describe the structural analysis of women's poetry in Suara 'Aisyiyah magazine published in 2021. The research method used is a qualitative method by descriptive analysis, with the object of research in the form of three poems by Cheny Kurata A'yun entitled "Rain on a Prayer Mat", "Owner of Pertiwi" and "Hilang Arah" (2021). This study concludes that women's poems written in the 2021 publication period have a consistent physical and inner structure. This is characterized by the elements of construction with the presence of diction, imagery, majas, rhyme, typography, theme and mandate.